Evaluation of Education Management on Brawl among Students and How to Deal with It - Prita Febriani; Adiprana Yogatama (Universitas Negeri Semarang, 2023)
This study is prompted by observational data that reveals gains from the spread of brawl-related news on social media. Brawls amongst students have become a deeply ingrained custom for students in Indonesia, causing concern among some parents and the surrounding community. Data in this research was collected utilizing in-depth observation research methods, with researchers watching various news on social media and television. The Data is then processed and analysed using an inductive analytical descriptive method. As a result, the brawl was triggered because the two youth groups blasphemed each other on social media Instagram, which then they decided to meet and fight.